Ion, or, On the Iliad - Plato. (Amsterdam Studies in Classical Philology, 2007)
On the basis of a fresh collation of the four primary manuscripts, this book presents a revised text of Plato's Ion , with full apparatus criticus. The commentary has a strong linguistic orientation; it includes discussions of Platonic vocabulary. Linguistic considerations are also the leading principle in the choice of one MS reading rather than another. Drawing on Byzantine practices and theories, the book pays special attention to questions of punctuation, an area too often ignored in editions of classical texts. The extensive introduction deals with, inter alia, Plato's attack on poetry, the position of the Ion in the corpus Platonicum-rather late, this book argues-, the title(s) of the dialogue, the reasons why MS Venetus 189 should be considered a primary MS, and the text of the Homeric quotations in the Ion.